BRITISH’S HEGEMONY IN JOHN BRILEY’S ‘GANDHI’ - Muthia Yovani; Yuhendra; Rany Syafrina; Nofrika Sari; Haris Syukri (LLDIKTI Wilayah X, 2023)
This research examines colonialism in India, focusing on the British East India Company and the practice of hegemony. The study explores how the company shifted from trading to monopolizing India's economy. Postcolonial theory and literature are analyzed as tools to understand the effects of European colonialism on society, culture, and history. The concept of hegemony is explored as a form of dominance exerted by the colonizers over the colonized. Mahatma Gandhi's non-violent resistance is highlighted as a struggle against British cultural and economic hegemony. The research employed qualitative methods, utilizing close reading and library research. This study contributes to understanding colonial dynamics and the impact of hegemony in India. The writer of Gandhi found how British colonizers influenced India, the colonization with their ideology that distinguished between white and colored people, also known as hegemony. The aspect of this hegemony is the general conception of life, which represents